Cross-cultural development of a quality-of-life measure for patients with melanoma. Issue 1 (February 2015) - Winstanley, Julie B.; Young, Teresa E.; Boyle, Frances M.; Bergenmar, Mia; Bottomley, Andrew; Burmeister, Bryan; Campana, Luca G.; Garioch, Jennifer J.; King, Madeleine; Nikolic, Dejan V.; van de Poll-Franse, Lonneke V.; Saw, Robyn; et al.
<x xml:space="preserve">Abstract</x> Melanoma is an increasingly common skin cancer worldwide. Recent treatment advances have provided patients and healthcare professionals (HCPs) with choices where quality of life (QoL) and toxicity are important considerations. A melanoma-specific QoL questionnaire is being developed in a cross-cultural setting using a four phase process developed by the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Group. In phase 1, a literature search identified a list of pertinent QoL issues; this was shown to HCPs and patients in eight countries and rated for importance and relevance. Questions were constructed for the highest-rated issues (phase 2) and piloted in another patient sample (phase 3). Using EORTC Quality of Life Group criteria and sequential use of factor and Rasch analysis, scales were hypothesized for field testing (phase 4). Seven QoL domains (disease symptoms, treatment issues, financial issues, access/quality of information, satisfaction with care, psychosocial issues and support), comprising 73 QoL issues, were rated by 46 HCPs and 78 patients. Fifty-six issues were rephrased as questions and piloted with 132 patients. A 38-item questionnaire (QLQ-MEL38) is available for field testing in conjunction with the EORTC QLQ-C30. This study has shown that melanoma patients have important QoL issues that have been incorporated into a new cross-culturally validated instrument. Future testing of this EORTC module is planned and will be an important step forward in providing reliable QoL data to aid future decision-making in the management and clinical trials of this complex group of patients.